TINJAUAN FIQH MUNAKAHAT TERHADAP PERKAWINAN TUNAGRAHITA - Irwansyahlubis; M. Sidik; Zenal Setiawan (JURNAL CERDAS HUKUM, 2022)
Marriage is the desire and desire of every human being. And the Prophet Muhammad was very proud of his people who got married. And let the person you want to marry is a healthy and fertile person. However, no one knows the fate of a person, that not a few people are also suffering from mental retardation and disabilities and so on, or in today's terms called mental retardation. Although people who suffer from mental retardation do not recover from their illness. So that does not mean his heart closed his desire to get married. Because even though they have disabilities and retardation, if their minds are still normal, it can be ascertained that they still want marriage to occur at least once in their life. In general, Islamic law does not prohibit marriage for people who are mentally handicapped or mentally retarded. Because even in the munakahat fiqh review, marriage is said to be valid if the terms and pillars of marriage that have been agreed upon by the ulama are carried out and implemented. On the other hand, if the pillars and requirements are not fulfilled, even though the bride and groom are normal, then the marriage is considered null and void.